Nursing of a patient with sudden deafness using Orem self-care mode combined with Traditional Chinese medicine interventions (Orem自理模式联合中医疗法应用于1例突发性聋患者的护理体会) - SONG Bo (宋波); MEI Xueting (梅雪婷); PEI Xiaolu (裴晓璐); WANG Junge (王俊阁); AI Jianwei (艾建伟); YAN Xinyu (闫新宇); HAN Jinshuai (韩金帅) (中西医结合护理)
This article retrospectively analyzed the nursing process of a patient with sudden deafness was treated with Orem self-care mode combined with Traditional Chinese medicine interventions. In response to the problems of affected quality of life, easy occurrence of adverse emotions, and decreased self-care ability of the patient, the Orem self-care mode was used to guide the nursing practice. A complete/partial compensation system and a supportive education system were established. At the same time, Traditional Chinese medicine interventions such as auricular acupoint pressing and Chinese herbal medicine fumigation were provided to improve the recovery of hearing, relieve the anxiety status, and enhance the self-care ability of the patient. (本文总结1例突发性聋患者采用Orem自理模式联合中医疗法治疗及护理体会。患者入院后完善相关检查和护理评估, 组建Orem自理模式干预护理小组, 实施完全/部分补偿系统及支持教育系统干预, 并给予耳穴压丸及中药泡洗等中医外治法, 有效改善患者听力, 缓解焦虑情绪, 提升自理能力。)